Clinical manifestations and hematological and serological findings in children with dengue infection - Mulya Rahma Karyanti (Indonesian Pediatric Society, 2011)
Background Dengue hemorrhagic fever (DHF) is endemic to Indonesia and remains a public health problem, with its highest incidence in children. There have been few reports on the clinical, hematological and serological data in children lith dengue.Objective To assess the clinical and laboratory profiles of children lith dengue infection in Cipto Mangunkusumo Hospital, Jakarta, Indonesia.Methods Clinical, hematological and serological infonnation from children diagnosed v.ith dengue infection in Cipto Mangunkusumo Hospital were collected from 2007 to 2009.Results Of611 children admitted with dengue, 143 (23.4%) had dengue fever (DF), 252 (41.2%) had DHF grades I and II; and 216 (35.4%) had DHF grades III and IV. Of the 81 cases where dengue serotypes were identified, 12.3% were DENV1, 35.8% were DENV-2, 48.2% were DENV-3 and 3.7% were DENV-4. Mean age of subjects was 8.9 years (SD 4.4), and 48.4% of cases were boys. The mean length of fever before hospital admission was 4.2 days (SD 1.1) and mean length of stay in the hospital was 4 days (SD 2.7). Common symptoms observed were petechiae, hepatomegaly and epistaxis. Complications found mostly in those with dengue shock syndrome (DSS) were hematemesis (30 cases, 4.9% of all patients), encephalopathy (19 cases, 3.1 %) and melena (17 cases, 2.8%).Conclusion Signs and symptoms of fever, bleeding manifestations and thrombocytopenia were present in children 'With DF and DHF, while signs of increased vascular permeability were found only in those 'With DHF. Encephalopathy and gastrointestinal bleeding were found mostly in DSS cases. At admission, leukopenia was found in more DF patients than in DHF patients. Absence of leukopenia may be a sign of more severe dengue infection.